Gambaran Remaja yang Kecanduan Pornografi di Sekolah Menengah Kejuruan Negeri 1 Kota Serang - Aisyah Sekar Tri Wardani; Syafrizal Syafrizal; John Pahamzah; Mochammad Thamrin Yahya; Mohammad Jordan Feshilal Antarik; Risa Alifia; Akmal Suropriyono; Triana Febriyani Lestari (Pusat Riset dan Inovasi Nasional, 2025)
Teenage morality is at risk, because once that horizon-opening advanced cell phone is in unsafe hands, all windows are open regardless of good or bad. Pornography addiction can negatively affect adolescents by disrupting their social lives, emotions, and cognitive processes. This study aims to find a picture of adolescents who are addicted to pornography at SMKN 1 Serang City. The research method used is descriptive qualitative. These data were obtained from journals, articles, survey results, and interviews. This study used semi-structured interviews to explore in-depth information about adolescents' experiences of access to and addiction to pornographic content. The results show that addiction to pornographic content among teenagers at SMKN 1 Serang City generally starts at a very young age, around elementary school age. Students at SMKN 1 Serang City, the majority do not feel the influence of pornographic content in the school environment, although there are a small number of students who are influenced by seniors. Some students feel that pornographic content does not really interfere with their learning focus or social relationships, but others admit to being emotionally disturbed and their learning concentration.